Effectiveness of acceptance and commitment therapy-based interventions for improving the psychological health of parents of children with special health care needs: A systematic review and meta-analysis - Sini Li; Zengyu Chen; Yijing Yong; Jiao Xie; Yamin Li (Comprehensive Psychiatry, 2023)
Purpose: To evaluate the effectiveness of ACT-based interventions on improving the mental health of parents of children with SHCN compared to active/inactive controls and to investigate the characteristics/components of the effective interventions in the included studies. Methods: Eight databases were searched from inception to 14 February 2023. We included all randomized controlled trials (RCTs) of ACT-based interventions for parents of children with SHCN published in English or Chinese journals and dissertations reporting at least one parental mental health outcome postintervention. Results: Fourteen RCTs were included. The results indicated significant improvements of ACT-based interventions in the stress (Hedges' g = −0.36), depressive symptoms (g = −0.32), anxiety (g = −0.29), distress (g = −0.29), psychological flexibility (g = 0.51), mindful awareness/mindfulness abilities (g = 0.41), and confidence/self-efficacy (g = 0.30) of parents, as well as in the emotional and behavioural problems (EBP; g = −0.39) of their children with SHCN postintervention, with moderate to high certainty of evidence. Furthermore, the optimal components of ACT-based interventions, including the intervention approaches (ACT combined with another parenting technique/program), active participants (only involving parents), delivery mode (in-person) and format (group-based format), and desirable number of sessions (4–8 sessions), were identified to inform the design of future interventions/studies. Conclusion: This review highlights the positive effects of ACT-based interventions on mental health, psychological flexibility, mindful awareness/mindfulness abilities, and confidence/self-efficacy in parents and EBP in children with SHCN. Since group-based ACT combined with a parenting technique/program was identified as the optimal effective strategy, its effects could be further examined in larger-scale RCTs with parents and children with SHCN with diverse ethnic and sociodemographic characteristics.